2019
DOI: 10.1002/hep.30482
|View full text |Cite
|
Sign up to set email alerts
|

Tremelimumab in Combination With Microwave Ablation in Patients With Refractory Biliary Tract Cancer

Abstract: Treatment options for patients with advanced biliary tract cancer are limited. Dysregulation of the immune system plays an important role in the pathogenesis of biliary tract cancer (BTC). This study aimed to investigate whether tremelimumab, an anti-CTLA4 (cytotoxic T-lymphocyte-associated protein 4) inhibitor, could be combined safely with microwave ablation to enhance the effect of anti-CTLA4 treatment in patients with advanced BTC. Patients were enrolled to receive monthly tremelimumab (10 mg/kg, intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 30 publications
1
59
1
Order By: Relevance
“…In recent years there has been an increasing wariness that loco-therapies may eliminate not only tumors but also have additional systemic effects ( 16 , 33 ). Some studies described the immunological “abscopal effects” induced by loco-therapies and a range of cytokine and chemokine changed following various ablative procedures, suggesting that once the immune response is triggered the effects could be potentially amplified by immunotherapy ( 16 , 17 , 34 , 35 ). Our study confirmed the hypothesis and found additional ablation enhanced the antitumor effects of anti-PD-1 inhibitors and increased the response rate.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been an increasing wariness that loco-therapies may eliminate not only tumors but also have additional systemic effects ( 16 , 33 ). Some studies described the immunological “abscopal effects” induced by loco-therapies and a range of cytokine and chemokine changed following various ablative procedures, suggesting that once the immune response is triggered the effects could be potentially amplified by immunotherapy ( 16 , 17 , 34 , 35 ). Our study confirmed the hypothesis and found additional ablation enhanced the antitumor effects of anti-PD-1 inhibitors and increased the response rate.…”
Section: Discussionmentioning
confidence: 99%
“…Combined regimens of anti-PD-L1/PD-1 checkpoint agents with other therapies have also been increasingly practiced in clinic, including additional immunotherapies, chemotherapy, and targeted therapies. [254][255][256][257][258][259][260] In a phase I study led by Xie's group (NCT01853618) showed that PFS and OS were 3.4 months (95% CI 2.5-5.2) and 6.0 months (95% CI 3.8-8.8), 261 which declared that tremelimumab (anti-CTLA-4 monoclonal antibody (mAb)) is a potential treatment strategy for patients with advanced BTC. A phase I study (NCT01938612) evaluated durvalumab (anti-PD-L1 mAb) with/without tremelimumab in Asian GBC patients.…”
Section: Pd-1/pd-l1mentioning
confidence: 99%
“…Although conclusions are limited from this small study, there was some correlation between markers of immune activation and clinical response (HLA-DR+). 106 Combination of immune checkpoint blockade and cytotoxic chemotherapy Chemotherapy can also increase tumour neoantigen release by direct tumour cell killing, and alters TIME through cytotoxicity of immune subsets. MDSCs can be eliminated by chemotherapy, providing a rationale for combining cytotoxic chemotherapy with ICB or other immunotherapy.…”
Section: Combination Of Immune Checkpoint Blockade and Local Ablativementioning
confidence: 99%